2015
DOI: 10.15288/jsad.2015.76.594
|View full text |Cite
|
Sign up to set email alerts
|

The Chicken or the Egg: Examining Temporal Precedence Among Attitudes, Injunctive Norms, and College Student Drinking

Abstract: ABSTRACT. Objective: The present study was designed to test for projection, conformity, or reciprocal associations among attitudes, injunctive norms, and drinking. Assuming that these constructs are not independent, we proposed three possible trajectories. A conformity model would suggest that injunctive norms should temporally precede drinking or attitudes. Alternatively, a projection model would suggest that attitudes or alcohol use would precede injunctive norms. Furthermore, by examining the processes over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…In addition, SAM users, compared with nonusers, reported higher SAM use norm perceptions as did those who engaged in SAM use frequently compared with infrequently. Thus, consistent with the previous literature on alcohol and marijuana use (e.g., Lewis et al., 2015a; Wolfson, ), those who report heavier SAM use also report higher normative perceptions.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, SAM users, compared with nonusers, reported higher SAM use norm perceptions as did those who engaged in SAM use frequently compared with infrequently. Thus, consistent with the previous literature on alcohol and marijuana use (e.g., Lewis et al., 2015a; Wolfson, ), those who report heavier SAM use also report higher normative perceptions.…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, during years when an adolescent's alcohol use was higher than usual, perceived descriptive and injunctive norms increased the following year. These findings are the first to demonstrate reciprocal associations between descriptive and injunctive norms and alcohol use on the within‐person level of analysis and are consistent with prior studies assessing reciprocal effects on the between‐person level of analysis (e.g., Lewis et al., ; Marks et al., ; Wardell & Read, ). Moreover, support for reciprocal associations between perceived drinking norms and alcohol use from early through late adolescence supports reciprocal determinism in that social norms and alcohol use both shape and are shaped by one another.…”
Section: Discussionsupporting
confidence: 87%
“…To date, studies assessing reciprocal determinism for social norms and alcohol use have predominantly used college samples (e.g., Lee, Geisner, Patrick, & Neighbors, 2010;Lewis, Litt, & Neighbors, 2015), despite the evidence that norms are particularly dynamic during adolescence. Only one study, to our knowledge, has examined reciprocal effects between adolescent social norms and alcohol use.…”
Section: The Development Of Social Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research examining the temporal relationships between perceived norms and drinking have shown direct effects of perceived descriptive and injunctive norms on subsequent drinking behavior among youth (Elek, Miller-Day, & Hecht, 2006; Larimer et al, 2004). However, there is also evidence of a reciprocal relationship, with perceived descriptive and injunctive norms predicting subsequent drinking, and also concurrent drinking predicting subsequent perceived norms (Lewis, Litt & Neighbors, 2015; Neighbors, Dillard, Lewis, Bergstrom & Neil, 2006; Wardell & Read, 2013). Future research should also examine perceived benefits within a longitudinal context to better understand the dynamic interplay of these moderators.…”
Section: Discussionmentioning
confidence: 99%